Rural Superintendents’ Responses to COVID-19: Navigating Local Control During a Public Health Crisis - Lochmiller, Chad R. (Frontiers in Education, 2021)
The COVID-19 pandemic has prompted a variety of responses by organizational leaders throughout the United States and internationally. This paper explores the responses of five rural school superintendents who work in a conservative Midwestern state. Using an exploratory qualitative research design, the study analyzes interviews and documents collected remotely to adhere to current public health guidelines. The study adopted a crisis leadership perspective to explore how rural school superintendents were responding to the COVID-19 pandemic and managing the politics associated with it. Findings suggest that superintendents were acutely aware of their community’s current political stance toward the COVID-19 pandemic and were especially responsive to the individual political philosophies of their elected school board members. The superintendents did not uniformly adopt crisis leadership behaviors to respond to the circumstances created by the pandemic. Rather, superintendents responded in ways that managed the political perspectives held by their elected board members and sought to reconcile differences in the board members’ political perspectives that precluded action. As part of this reconciliation, the superintendents leveraged public health information to shape and at times change elected school board members’ perspectives. This information helped the superintendents overcome political perspectives that led some of the most conservative board members to resist widely accepted public health guidance. Implications for the field of educational leadership, research on rural superintendents, and potential revisions to superintendent preparation are discussed.